Business Management Training For The Milk Candy Business Group In Penyaring Village, Sumbawa Regency - Silvia Firda Utami; Mietra Anggara; Ulfaturrahmi Ulfaturrahmi (International Journal Of Community Service, 2024)
Downstreaming of cattle farming products in the form of milk candy products continues to develop in Penyaring Village, Sumbawa district. This product is a characteristic of Sumbawa which is driving the economy of Penyaring Village. The demand for this product continues to increase all the time, making this product a typical souvenir that is very popular with local and foreign tourists. However, on average the milk candy business group does not have good business management, such as not having an organizational structure, a production system that is still manual, product marketing that is still manual and product quality is not good, making it very difficult to develop. For this reason, it is necessary to empower business groups by carrying out training and business management assistance consisting of organizational management, production management, quality management, and product marketing management to increase the income of the milk candy business group.  The Service Team surveyed milk candy business groups, assessing business management training as very useful and helpful in increasing income.